Information System Of Student Rangking Management Of Faculty Of Engineering In Univercity Of Gorontalo - Anissa Nurdin; Lillyan Hadjaratie; Roviana Dai (Gorontalo State University, 2021)
The present study was heavily motivated by the problems that often occurred in the students' affairs of the Faculty of Engineering, Universitas Negeri Gorontalo. The process of student ranking in the students' affair unit of the Faculty of Engineering employs a manual method of data collection of students' achievements. All files of students' achievements are photocopied, scanned, and archived into a computer. This method is lacking in a crucial aspect; students with achievements or recognitions cannot input and archive their achievements into the university database by themselves. Therefore, the data of achievements might get scattered and hinder the evaluation process. The study employed a prototype method. The results showed that an information system of student ranking management was developed to assist the compilation process of students' achievements. By the developed information system, the students are enabled to input the achievements they have into the system by themselves.Keywords: Management, Ranking, Student Ranking Management Information System, Prototype